Discovery of orally active hepatoselective glucokinase activators for treatment of Type II Diabetes Mellitus. Issue 9 (1st May 2017) - Xu, Jiayi; Lin, Songnian; Myers, Robert W.; Trujillo, Maria E.; Pachanski, Michele J.; Malkani, Sunita; Chen, Hsuan-shen; Chen, Zhesheng; Campbell, Brian; Eiermann, George J.; Elowe, Nadine; Farrer, Brian T.; et al.
Graphical abstract: Abstract: Systemically acting glucokinase activators (GKA) have been demonstrated in clinical trials to effectively lower blood glucose in patients with type II diabetes. However, mechanism-based hypoglycemia is a major adverse effect that limits the therapeutic potential of these agents. We hypothesized that the predominant mechanism leading to hypoglycemia is GKA-induced excessive insulin secretion from pancreatic β-cells at (sub-)euglycemic levels. We further hypothesized that restricting GK activation to hepatocytes would maintain glucose-lowering efficacy while significantly reducing hypoglycemic risk. Here we report the discovery of a novel series of carboxylic acid substituted GKAs based on pyridine-2-carboxamide. These GKAs exhibit preferential distribution to the liver versus the pancreas in mice. SAR studies led to the identification of a potent and orally active hepatoselective GKA, compound6 . GKA6 demonstrated robust glucose lowering efficacy in high fat diet-fed mice at doses ⩾10 mpk, with ⩾70-fold liver:pancreas distribution, minimal effects on plasma insulin levels, and significantly reduced risk of hypoglycemia.